Bacterial diversity, community structure and function in association of potato scabby tubers during storage in northern Thailand - Macharoen, Pipat; Mhuantong, Wuttichai; Wannawong, Thippawan; Leesutthiphonchai, Wiphawee; Tanasupawat, Somboon; Suwannarach, Nakarin; Kuncharoen, Nattakorn (Folia microbiologica, 2024)
Potato scab is a common potato tuber disease that affects quality and cost in the marketplace, shortening storage, and increasing the chance for secondary infection. The tubers with disease severity of 1 to 4 are accepted and stored in potato storage for cheap selling in Thailand. However, there are few studies of the bacterial community of the scabby tuber during storage. Thus, we aim to elucidate the diversity, structure, and function of the bacterial community of 30-day storage potato scabby tubers stored in different temperatures using 16S amplicon metagenomic sequencing. Bacterial communities of storage potato scabby tubers (Spunta cultivar) collected from different storage temperatures, 4 °C (MEP1) and 6 °C (MEP2), were characterized using 16S rRNA amplicon metagenomic sequencing. The alpha-diversity abundance in the bacteriome of the scabby tubers stored at 6 °C was higher than in those stored at 4 °C. Actinobacteria (34.7%) was a dominant phylum in MEP1, while Proteobacteria (39.9%) was predominant in MEP2. The top 10 genera of both communities were Rhizobium group, Streptomyces, Pectobacterium, Ruminococcus, Cellulomonas, Promicromonospora, Prevotella, Enterobacter, Pedobacter, and Paenarthrobacter. Moreover, functional profile prediction of both communities reveals essential genes in the pathosystem: nos, bglA, and cebEFG-msiK for potato scab disease and phc and peh operons for rot disease. Our findings are the first study to explore details of the bacteriome of the accepted potato scabby tubers for selling during storage in Thailand and strongly indicate that although potatoes were stored at low temperatures, diseases still occur by secondary pathogens.
Keywords: RNA ribozomální 16S; metagenomika; Bacteria; Temperature; nemoci rostlin; DNA bakterií; Potato scabby tubers; skladování potravin; Food Storage; Bacterial diversity; Thailand; Plant Diseases; RNA, Ribosomal, 16S; fylogeneze; DNA, Bacterial; Plant pathogenic bacteria; Functional gene profile; teplota; biodiverzita; Plant Tubers; Metagenomics; Thajsko; Amplicon metagenomic sequencing; mikrobiota; Microbiota; hlízy rostlin; Bacterial community structure; Solanum tuberosum; Phylogeny; Biodiversity